2013
DOI: 10.1111/gtc.12055
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II‐induced cardiac hypertrophy and fibrosis are promoted in mice lacking Fgf16

Abstract: Fibroblast growth factors (Fgfs) are pleiotropic proteins involved in development, repair and metabolism. Fgf16 is predominantly expressed in the heart. However, as the heart function is essentially normal in Fgf16 knockout mice, its role has remained unclear. To elucidate the pathophysiological role of Fgf16 in the heart, we examined angiotensin II-induced cardiac hypertrophy and fibrosis in Fgf16 knockout mice. Angiotensin II-induced cardiac hypertrophy and fibrosis were significantly promoted by enhancing T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 30 publications
2
48
1
Order By: Relevance
“…Previous studies using FGF2-deficient and -overexpressing mutant mice have shown that FGF2 is a critical mediator of cardiac hypertrophy in response to transaortic constriction (TAC) or renal-induced hypertension (37)(38)(39). Similar to the expression of CTGF, FGF2 is mainly synthesized by CFs in response to myocardial stress (40,41). We found that the expression of FGF2 and other hypertrophic markers, as well as the activation of ERK and p38 MAPK, were increased in heart tissues after Ang II infusion.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies using FGF2-deficient and -overexpressing mutant mice have shown that FGF2 is a critical mediator of cardiac hypertrophy in response to transaortic constriction (TAC) or renal-induced hypertension (37)(38)(39). Similar to the expression of CTGF, FGF2 is mainly synthesized by CFs in response to myocardial stress (40,41). We found that the expression of FGF2 and other hypertrophic markers, as well as the activation of ERK and p38 MAPK, were increased in heart tissues after Ang II infusion.…”
Section: Discussionmentioning
confidence: 61%
“…Importantly, previous reports showed that FGF2 is expressed in non-cardiomyocytes and has a positive effect on cardiomyocyte replication, angiogenesis, collagen synthesis, and infarct repair or hypertrophy (Kaye et al, 1996;Virag et al, 2007;House et al, 2010). It has been reported that FGF16 blocks FGF2 function by competing with FGF2 for binding to its receptor FGFR1c (FGF receptor 1c) (Lu et al, 2008), and in doing so might, therefore, inhibit cardiac hypertrophy and fibrosis (Matsumoto et al, 2013;Santiago et al, 2014). Altogether, previous findings indicate that FGF16 in the extracellular matrix might promote the inhibition of fibrosis and hypertrophy, or provide a niche for cardiac progenitors to drive regeneration.…”
Section: Discussionmentioning
confidence: 92%
“…FGF-16 can bind to FGFR1, but also other FGFRs with high affinity [14,56]. FGF-16 does not appear, however, to have a strong effect on postnatal cardiac myocyte proliferation, based on exogenous treatment of neonatal rat cardiac myocyte cultures and the cardiac phenotype of FGF-16 null C57BL/6 mice [14,57]. The fact that FGF-16 can bind multiple FGFRs raises the possibility of both shared but also antagonistic function with other FGF family member and affecting signaling.…”
Section: Endogenous Fgf-16 Helps Maintain a Healthy Myocardiummentioning
confidence: 99%